Les traductions russes de La Légende de Saint Julien L’Hospitalier - Svetlana Maire (Flaubert: Revue Critique et Génétique)
The Russian reader has always been lost in admiration at Gustave Flaubert’s production, which is particularly style-worked and of a high literary quality. The Legend of St. Julian the Hospitaller, wrote in 1876, is marked out by stylistic treasures where the form is also important as the content. Consequently, this text represents a difficult translation exercise. However, the text has always aroused interest of translators. It was in the year 1877 that Ivan Turgenev first translated it into Russian and after that various versions with distinctive features have been turning up. This paper consists on examining three versions carried out for the three different periods by three eminent personalities of the Russian literature, Ivan Turgenev, Alexandr Blok, Maximilian Vološin. Each of them has his own translation method, uses his own devices in order to restore as best as possible Flaubert’s stylized descriptions. The temporal distance, which exists between three translations, supposes that each of them follow the literary trends peculiar for their period. So, the comparative analysis of the translations is going to be made under a diachronic angle. Besides, the translation of each of them reflects dominant trends in the development of the various conceptions of the translator’s profession and more particularly on the work of the historic stylization.